Effect and Mechanisms of Spice Marination on the Formation of Hazards in Roasted Fish - CHE Jing, WANG Bo, CUI Shuang, HUANG Xuhui, QIN Lei (Shipin Kexue)
In this study, the hazards and thermal reaction products were monitored in roasted fish marinated with spices. Correlation analysis and dimensionality reduction analysis were carried out using multivariate statistical analysis methods to explore the effect and mechanism of spices on the generation of multiple hazards in roasted fish, aiming to improve the safety of roasted fish through marinating with spices. The results indicated that six spices, including thyme, prickly ash, red pepper, bay leaf, dried ginger, and black pepper, had a certain inhibitory effect on hazards in roasted fish. The highest inhibitory rates of heterocyclic amines (HAAs), acrylamide (ACY), 5-hydroxymethylfurfural (5-HMF), and polycyclic aromatic hydrocarbons (PAHs) were 65.51%, 61.71%, 35.02%, and 35.10%, respectively. Collectively, black pepper and red pepper had better inhibitory effects. Through non-targeted omics analysis of the thermal reaction products in roasted fish, it was found that various hazards in roasted fish were positively correlated with heterocyclic compounds but negatively correlated with organic acids and their derivatives. It was speculated that spices could reduce the formation of hazards by reducing heterocyclic compounds and increasing organic acids and their derivatives in roasted fish.